Initial evaluation of thyroid nodules by primary care physicians and internal medicine residents - Quianzon, Celeste C. L. (J Community Hosp Intern Med Perspect, 2015)
OBJECTIVE: The article studied the knowledge and practice patterns of primary care providers and internal medicine residents in their initial evaluation of thyroid nodules and determined whether their practice is in accordance with published guidelines by the American Thyroid Association and American Association of Clinical Endocrinologists. METHOD: A survey was distributed to primary care physicians (PCPs) and internal medicine residents at a community hospital in Baltimore and a chart review was conducted at the Diabetes and Endocrine Center in the same hospital. RESULTS: A total of 47 physicians (70%) responded to the survey, 16 PCPs and 33 residents. Most responders (96%) will always obtain a TSH, and of these, 21% of PCP and 25% of residents will obtain a TSH without any other laboratory work-up. Fifty percent of the physicians (PCP, 75%; resident, 39%) will always obtain a thyroid ultrasound (p=0.043). Most physicians (97%) will refer for a fine-needle aspiration (FNA) biopsy of a nodule >1 cm. Sixty-two percent of the physicians will not put a euthyroid patient on levothyroxine suppression therapy. Many physicians (48%) are not aware of the AACE and ATA thyroid nodule guidelines. Most physicians (65%) have not read the guidelines. Of the 113 charts reviewed, TSH was obtained alone in 40% and with other laboratory tests in 74%. Thyroid ultrasound was done in 67%. Only one patient was on levothyroxine for levothyroxine suppression therapy. DISCUSSION: Although many physicians were not aware of the guidelines, and a small number of physicians have read them, many PCP and residents responded in concordance with the guidelines in obtaining TSH, an ultrasound, performing FNA biopsy, and not providing levothyroxine suppressive therapy in euthyroid patients. No differences were found between the responses of PCP and residents except for obtaining an ultrasound. Chart review data also showed that majority of tests ordered for non-toxic thyroid nodule evaluation were in agreement with the guidelines. Limitations include low survey response rate among PCPs and that results are from one community hospital. CONCLUSION: Our findings from the survey and chart review conclude that majority of primary care physicians were initiating the appropriate work up of thyroid nodules prior to referral to a specialist.